Theoretical Viewpoints on Women's Segregation in the Workplaces - Muhammad Wayong (JICSA : Journal of Islamic Civilization in Southeast Asian, 2016)
This paper depicts the vertical and horizontal segregation of women in the work places. It overviews the question of gender segregation both in developed and in the developing countries, particularly in the case of Indonesia. Female workers need bargaining power – their knowledge about working conditions and their skills to organize at work – in order to get well paid, high status jobs with good career opportunities. The low level of women’s wage is assumed to be related to the levels of human capital such as education, training, and skill embodied in women.